(untitled) (Journal of Numerical Optimization and Technology Management, 2023)
This research aims to investigate the influence of return on assets, return on equity and net profit margin on economic growth in Malaysia. The secondary data for this study were collected from annual reports of the five full-fledged Islamic banks in Malaysia for six years (2016-2021). This study employs panel data regression by indicating a random effect model as the best estimator. The findings of the panel regression analysis show return on assets (ROA) and net profit margin (NPM) of full-fledged Islamic banks in Malaysia have positive and significant effects on economic growth. Therefore, this proves solid evidence that Islamic banking institutions and their financial performances are one of Malaysia’s economic growth channels. It will motivate many people to go for Islamic banking rather than conventional ones, given its contribution to the country’s economic growth. From another perspective, Islamic banks too will inspire and be taken into consideration by the conventional banks towards opening Islamic windows to meet Malaysian’s growing demand.